2023
DOI: 10.1590/2179-8087-floram-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Energy Quality of Wood and Charcoal from the Stem and Root of Eucalyptus spp.

Abstract: This work aimed to evaluate the energy quality of wood and charcoal obtained from the stem and root of the genus Eucalyptus spp. From the wood, the physical, chemical and energetic properties were evaluated. For the charcoal produced in ovens of the carbonization furnaces model in the industry and produced in a muffle furnace, the physical, chemical and energetic properties were evaluated. Based on the analysis of technological properties, wood from the root has higher basic density (731.45 kg m -3 ) and ligni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…The lowest and highest values were given by Padus racemosa branchwood and Crataegus pinnatifida rootwood, respectively (Figure 2a). Our study and others [25] demonstrate the difference in WD among tree parts that vary with species. Reasons for WD variation are complex.…”
Section: Interspecific and Intra-tree Differences In Wood Propertiessupporting
confidence: 77%
See 2 more Smart Citations
“…The lowest and highest values were given by Padus racemosa branchwood and Crataegus pinnatifida rootwood, respectively (Figure 2a). Our study and others [25] demonstrate the difference in WD among tree parts that vary with species. Reasons for WD variation are complex.…”
Section: Interspecific and Intra-tree Differences In Wood Propertiessupporting
confidence: 77%
“…From root to branch, the CD tended to decrease, indicating that root wood has a higher C sequestration capacity than other parts of trees, except Malus baccata trees. The study of [25] found that the fixed carbon content of the root was lower than of the stem wood of the genus Eucalyptus spp. Without a doubt, this result improved our confidence in using four other Rosaceae species except Malus baccata to fix C in soil.…”
Section: Interspecific and Intra-tree Differences In CDmentioning
confidence: 97%
See 1 more Smart Citation